FORMATION AND DEVELOPMENT OF THE PHILOSOPHICAL ANTHROPOLOGY STUDIES IN SOVIET UKRAINE - S. V. Rudenko; V. E. Turenko (Antropologìčnì Vimìri Fìlosofsʹkih Doslìdžen')
Purpose of this article is the historical reconstruction of the studies in philosophical anthropology in Soviet Ukraine. Theoretical basis. In the philosophical tradition of independent Ukraine, there is an opinion that at the intersection of the 1960s and 1970s, there was an anthropological turn in the national philosophical thought. The authors provide a holistic and comprehensive reconstruction of philosophical understanding of man in the works of Ukrainian thinkers of the Soviet era. Originality. It has been proved that before the emergence of the Institute of Philosophy of the Soviet Ukraine Academy of Sciences and the restoration of the Philosophy Department at Kyiv State University, the writings of Ukrainian philosophers in the 1920s and 1930s emphasize specifically the "ideological" factor of human existence. Based on the materials of M. Maksymovych Academic Library and the library at H. Skovoroda Institute of Philosophy of the National Academy of Sciences of Ukraine, there have been revealed and traced the specific features and peculiarities of the transformation of main accents in philosophical and anthropological studies of Soviet Ukrainian researchers in the post-war period. Conclusions. The studied problems developed in Soviet Ukraine in two vectors. The focus was on man as a social phenomenon and a "product of ideology" on the one hand, and, on existential aspects of a human being with its internal contradictions, understanding of its nature and the sense of existence, on the other hand. It has been established that the anthropological problems were the focus of not only scientists of the Institute of Philosophy of the Soviet Ukraine Academy of Sciences (Y. Andros, N. Holovko, P. Kopnin, Y. Ohrimenko, L. Sokhan, V. Tabachkovskyi, V. Shynkaruk), but also of teachers of Kyiv State University (F. Baikin, I. Bychko, M. Duchenko, I. Nadolnyi). The authors grounded the thesis that, unlike the 1940-1950s, when the focus was on philosophical problems of natural science and philosophical personology, the 1960s bring forward not only philosophical and anthropological studies but also ethical and aesthetic issues, logic and scientific atheism.